2013
DOI: 10.1016/j.aju.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tamsulosin vs. alfuzosin as medical expulsive therapy for ureteric stones

Abstract: ObjectiveTo evaluate and compare the efficacy of tamsulosin and alfuzosin as medical expulsive therapy for ureteric stones.Patients and methodsIn all, 112 patients with ureteric stones of ⩽10 mm, located along the ureter, were randomly divided into three groups. In group I, 32 patients received no α-blockers (controls), in group II 40 patients received tamsulosin 0.4 mg daily, and in group III 40 patients received alfuzosin 10 mg daily. All patients were given analgesia and antibiotics when indicated. The foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
0
19
1
Order By: Relevance
“…As to safety, both combinations were well tolerated by the patients. Ibrahim et al [21] similarly reported minor therapy-related side-effects in five patients taking tamsulosin and in six taking alfuzosin, which were mild and did not require the withdrawal of treatment in any patient. Patients who were not stone-free after the 4 weeks of follow-up were treated successfully with ureteroscopy.…”
Section: Discussionmentioning
confidence: 87%
“…As to safety, both combinations were well tolerated by the patients. Ibrahim et al [21] similarly reported minor therapy-related side-effects in five patients taking tamsulosin and in six taking alfuzosin, which were mild and did not require the withdrawal of treatment in any patient. Patients who were not stone-free after the 4 weeks of follow-up were treated successfully with ureteroscopy.…”
Section: Discussionmentioning
confidence: 87%
“…Results of quality assessment using the Cochrane Risk of Bias tool can be found in Figure 7. Overall, a high degree of bias was seen with only nine studies judged to be at low risk while 41 were judged to be intermediate risk and 17 high risk . The most common cause for bias was blinding of both participants and personnel and outcomes assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Medical expulsive therapy proved to facilitate passage for stones less than 10 mm along the whole ureter. [ 13 ] On the other hand, URS and SWL are currently the main interventional treatment options for symptomatic ureteral stones. Although URS is a more invasive option than SWL, it has a better success rate with an overall success rate extending from 85.6%[ 14 ] to 95.7%.…”
Section: Discussionmentioning
confidence: 99%